Stenting for Symptomatic Intracranial Vertebrobasilar Artery Stenosis in Northeast of China: A Single-Center Study - Wang, Zhongxiu; Wang, Chao; Li, Chao; Shi, Mingchao; Wang, Shouchun; Yang, Yi (Frontiers in Neurology, 2021)
Abstract Objective: We described the incidence of surgery related complications to evaluate the safety of endovascular therapy for severe symptomatic intracranial vertebral basilar artery stenosis (IVBS) in our stroke center in Northeast of China. Methods: Consecutive patients with symptomatic IVBS caused by 70-99% stenosis despite standard medical treatment of antiplatelet agents plus statin were enrolled. Either balloon-mounted stent or balloon pre-dilation plus self-expanding stent was performed. Clinical adverse events like stroke, transient ischemic attack (TIA), and death after the surgery. Radiological events like in-stent throm-bosis, dissection and guide wire perforation during the process were recorded as complications as well. The baseline characteristics and outcomes of patients among different Mori types were com-pared. Results: From January 2017 to December 2018, 97 patients with stroke or TIA due to intracranial IVBS were treated by stenting, including 30 patients with basilar artery (BA) stenosis, 55 patients with intracranial vertebral artery (V4) stenosis and 12 patients with V4-BA stenosis. The primary events include 2 intracranial hemorrhage (2.1%, 2/97), 7 ischemic events (7.2%, 7/97), and 2 death (2.1%, 2/97). The successful stent deployment rate was 98.9% (96/97). The Apollo stent was used more for Mori A lesions. Self-expanding stent was more used in Mori C lesions. Mori C lesions are more vulnerable to endovascular procedure and showed higher rate of complications than A(p=0.008) and B type (p=0.047). Conclusion: A high technical success rate of IVBS stenting can be achieved and the safety was ac-ceptable while Mori C lesions were more vulnerable to endovascular procedure and showed higher rate of complications than A and B type.